Language variation in the media of the Low Countries - Schramme, Annick (Acta Academica: Critical views on society, culture and politics, 2006)
Language policy is an essential part of national movements. This paper will demonstrate that the Flemish public broadcasting company has played an important role in the process of nation-building, through its use and dissemination of Standard Dutch. On the one hand, the public broadcaster wished to promote the Dutch language and culture. On the other, Standard Dutch was essentially imported from the Netherlands. The current flexibility in the media vis-à-vis the use of Standard Dutch reflects the changing role of the public broadcaster in general. In a competitive media context, entertainment has become more important, at the expense of the educational role of the public broadcaster. The analysis of this evolution is based on research into the personal archive of Johan Fleerackers, who for 12 years (1965-1977) was the chief advisor of several Flemish ministers of culture.